Vascular endothelial growth factor C induces angiogenesis in vivo - Cao, Yihai (The National Academy of Sciences, 1998)
Vascular endothelial growth factor C (VEGF-C) recently has been described to be a relatively specific growth factor for the lymphatic vascular system. Here we report that ectopic application of recombinant VEGF-C also has potent angiogenic effects in vivo. VEGF-C is sufficiently potent to stimulate neovascularization from limbal vessels in the mouse cornea. Similar to VEGF, the angiogenic response of corneas induced by VEGF-C is intensive, with a high density of new capillaries. However, the outgrowth of microvessels stimulated by VEGF-C was significantly longer than that induced by VEGF. In the developing embryo, VEGF-C was able to induce branch sprouts from the established blood vessels. VEGF-C also induced an elongated, spindle-like cell shape change and actin reorganization in both VEGF receptor (VEGFR)-2 and VEGFR-3-overexpressing endothelial cells, but not in VEGFR-1-expressing cells. Further, both VEGFR-2 and VEGFR-3 could mediate proliferative and chemotactic responses in endothelial cells on VEGF-C stimulation. Thus, VEGF-C may regulate physiological angiogenesis and participate in the development and progression of angiogenic diseases in addition to lymphangiogenesis.